Preclinical Atherosclerosis, Global Cardiovascular Risk and Cardiovascular Events. - Novo, Salvatore (Bentham Science Publishers, 2012)
This e-book outlines "preclinical athersclerosis" and its markers in clinical practice. It gives simple but clear information for a better stratification of global cardiovascular risk. The text serves as an important guide for medical professionals involved in the management of cardiovascular patients.